Intranasal Ketamine for Depression in Adults: A Systematic Review and Meta-Analysis of Randomized, Double-Blind, Placebo-Controlled Trials - An, Dongjiao; Wei, Changwei; Wang, Jing; Wu, Anshi (Frontiers in Psychology, 2021)
Background: There is growing interest in glutamatergic agents as a treatment for depression, especially intranasal ketamine, which has become a hot topic in recent years. We aimed to assess the efficacy and safety of intranasal ketamine in the treatment of major depressive disorder, especially treatment-resistance depression. Method: We searched Medline, EMBASE, and the Cochrane Library until 1 April 2020 to identify double-blind, randomized controlled trials with allocation concealment evaluating intranasal ketamine in major depressive episodes. Clinical remission, response and depressive symptoms were extracted by two independent raters. The outcome measures were MADRS score improved from baseline, clinical response and remission, dissociative symptoms, and Common adverse events. The Analyses employed a random-effects model. Results: Data were synthesized from five RCTs employing an intranasal esketamine and one RCT employing intranasal ketamine, representing 840 subjects in parallel arms and 18 subjects in cross-over designs [n=858 with major depressive disorder (MDD), n=792 with treatment resistant depression (TRD)]. WMD of MADRS score decreased was observed 6.16 (95% CI 4.44–7.88) in 2-4 hours, 9.96 (95% CI 8.97–10.95) in 24 hours, 4.09 (95% CI 2.18–6.00) in 28 days. The pooled RR was 3.55 (95% CI 1.5–8.38, z=2.89, p<0.001) for clinical remission and 3.22 (95% CI 1.85–5.61, z=4.14, p<0.001) for clinical response at 24 hours, while the pooled RR was 1.7 (95% CI 1.28–2.24 z=3.72, p<0.001) for clinical remission and 1.48 (95% CI 1.17–1.86, z=3.28, p<0.001) for clinical response at 28 days. Intranasal ketamine was associated with transient dissociative symptoms and common adverse events occurring, but no persistent psychosis or affective switches. Conclusion: Our meta-analysis suggests that repeatedly intranasal ketamine conducted a fast-onset antidepression effect in unipolar depression, while the mild and transient adverse effects were acceptable.